Enantioselective quantification of fluoxetine and norfluoxetine by HPLC in wastewater effluents - Ribeiro, Ana R. (2014)
Microbial degradation is the most important process to remove organic pollutants in Waste Water Treatment Plants. Regarding chiral compounds this process is normally enantioselective and needs the suitable analytical methodology to follow the removal of both enantiomers in an accurate way. Thus, this paper describes the development and validation of an enantioselective High Performance Liquid Chromatography with Fluorescence Detection (HPLC-FD) method for simultaneous analysis of fluoxetine (FLX) and norfluoxetine (NFLX) in wastewater effluents. Briefly, this method preconcentrated a small volume of wastewater samples (50 mL) on 500 mg Oasis MCX cartridges and used HPLC-FD with a vancomycin-based chiral stationary phase under reversed mode for analyses. The optimized mobile phase was EtOH/aqueous ammonium acetate buffer (92.5/7.5, v/v) at pH 6.8. The effect of EtOH percentage, buffer concentration, pH, column oven temperature and flow rate on chromatographic parameters was systematically investigated. The developed method was validated within the wastewater effluent used in microcosms laboratory assays. Linearity (R2 > 0.99), selectivity and sensitivity were achieved in the range of 4.0–60 ng mL 1 for enantiomers of FLX and 2.0–30 ng mL 1 for enantiomers of NFLX. The limits of detection were between 0.8 and 2.0 ng mL 1 and the limits of quantification were between 2.0 and 4.0 ng mL 1 for both enantiomers of FLX and the enantiomers of its demethylated metabolite NFLX. The validated method was successfully applied and proved to be robust to follow the degradation of both enantiomers of FLX in wastewater samples, during 46 days.